1997
DOI: 10.1136/bmj.314.7074.118
|View full text |Cite
|
Sign up to set email alerts
|

Thermographic changes in keyboard operators with chronic forearm pain

Abstract: Objective: To examine whether short stature through childhood represents a disadvantage at around 12 years. Design: Longitudinal non-intervention study of the physical and psychological development of children recruited from the community in 1986-7 after entry into primary school at age 5-6 years; this is the second psychometric assessment made in 1994-5 after entry into secondary school at age 11-13 years. Setting: Southampton and Winchester health districts. Subjects: 106 short normal children ( < 3rd centil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 4 publications
(3 reference statements)
1
33
0
1
Order By: Relevance
“…In connection with breast vascularization, especially in the upper limbs, injuries and other disorders are sometimes associated with sympathetic effects to the vasculature of the affected limb, which are secondary [33].…”
Section: Commentmentioning
confidence: 99%
“…In connection with breast vascularization, especially in the upper limbs, injuries and other disorders are sometimes associated with sympathetic effects to the vasculature of the affected limb, which are secondary [33].…”
Section: Commentmentioning
confidence: 99%
“…Pritchard et al [110] showed an impaired vasodilatation response of the brachial artery to forearm muscle activity in symptomatic subjects, resulting in a reduced blood flow. From the observation that hand temperature during typing increases more in controls than in symptomatic subjects, Sharma et al [120] and Gold et al [39] concluded that blood supply of the arm is diminished in patients, probably due to sympathetic disregulation.…”
Section: Clinical Findings: Signs and Symptomsmentioning
confidence: 99%
“…Vasoconstriction of the radial artery and lack of a vasodilatory response to exercise were found in patients (Pritchard et al 1999). Further, changes in skin temperature determined by thermography (i.e., far infrared images) showed reduced temperature in the afflicted region among patients with forearm pain, possibly reflecting sympathetic dysfunction (Sharma et al 1997;Gold et al 2009). …”
Section: Autonomic Aberrations In Chronic Neck-shoulder Pain: Recent mentioning
confidence: 99%